2022
DOI: 10.1007/s12325-022-02155-9
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Biologic Adherence, Persistence, and Monotherapy Comparisons in US Patients with Psoriasis: Results from IBM MarketScan® Databases

Abstract: Introduction Limited real-world data are available comparing multiple biologics on their adherence, persistence, and the use of concomitant biologics in the treatment of moderate-to-severe psoriasis in clinical practice. The objective was to compare persistence of and adherence to ixekizumab (IXE) treatment, as monotherapy or with concomitant medication, versus patients receiving other commonly prescribed biologics. Methods Patients who newly initiated IXE, adalimumab (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Accordingly, multiple (inter)national registries reported longer drug survival of IXE as well, followed by SEC survival, and -where applicable -lastly BRO. [18][19][20][53][54][55][56] Next, bio-naive IL-17i patients in our cohort demonstrated prolonged drug survival of approximately 10 months compared to bio-experienced patients (55.7 vs. 45.8 months, respectively), when pooled for all IL-17i. Similarly, bioexperience was related to shorter drug survival in other registries as well.…”
Section: Treatment Modificationmentioning
confidence: 62%
See 1 more Smart Citation
“…Accordingly, multiple (inter)national registries reported longer drug survival of IXE as well, followed by SEC survival, and -where applicable -lastly BRO. [18][19][20][53][54][55][56] Next, bio-naive IL-17i patients in our cohort demonstrated prolonged drug survival of approximately 10 months compared to bio-experienced patients (55.7 vs. 45.8 months, respectively), when pooled for all IL-17i. Similarly, bioexperience was related to shorter drug survival in other registries as well.…”
Section: Treatment Modificationmentioning
confidence: 62%
“…Still, IXE tended to have a higher survival, followed closely by SEC in the short term. Accordingly, multiple (inter)national registries reported longer drug survival of IXE as well, followed by SEC survival, and – where applicable – lastly BRO 18–20,53–56 …”
Section: Discussionmentioning
confidence: 95%
“…After adjusting for both ICER discounts and adherence, differences in mean index drug costs PPPM between IXE and SEC users declined from US$596 (US$3990 vs US$3394) to US$28 (US$3794 vs US$3766). This highlights the added benefits of higher treatment adherence among IXE users as both treatments are equally expensive and no significant differences in ICER-adjusted all-cause and psoriasis-related costs between IXE and SEC were observed [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advent of biologic agents over nearly two decades has dramatically enhanced the treatment of moderate to severe psoriasis. Data from randomized controlled trials (RCTs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] have demonstrated that these agents can be highly efficacious. Yet the preponderance of evidence has been garnered from studies that have primarily included White patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, while prior real-world evidence (RWE) studies have demonstrated the effectiveness of biologic therapies for psoriasis [4][5][6][7][8][9][10][11][12][13][14][15][16], there is little published data comparing the efficacy of biologics in Asian compared with other ethnicities in RWE studies. Real-world evidence is essential for providing insight into the efficacy and safety of drug treatments across all patients with psoriasis since the typical strict inclusion criteria of RCTs often exclude many patient populations seen in routine clinical care, including those with multiple comorbidities, ethnic and racial subpopulations, older adults, and patients for whom multiple biologics have failed.…”
Section: Introductionmentioning
confidence: 99%